Complications between early and standard oral feeding after pancreatico-enteric anastomosis - Monda, Satya Ranjan; Aman, Asif; Ullah, M. Meher; Ahmed, Jalal; Khan, Mohammad Emrul Hasan; Chowdhury, Ananya; Qurashi, Sabrina Akhter (International Surgery Journal, 2025)
Background: Pancreatico-enteric anastomosis is a complex and challenging surgical procedure. Early postoperative nutritional support plays a crucial role in minimizing complications and improving outcomes. The aim of this study was to compare the complications associated with early oral feeding and standard oral feeding following pancreatico-enteric anastomosis. Methods: This study was conducted at Dhaka Medical College Hospital (July 2023–June 2024) on patients undergoing pancreatico-enteric anastomosis. After consent, they were assigned to Group A (early feeding on POD 1–2) or Group B (standard feeding on POD 4-5). Serum albumin was measured preoperatively and on POD 3 and 7; serum and drain amylase were assessed on POD 3. Results: There were no significant differences in demographic characteristics between the groups. Pancreaticoduodenectomy was performed in 62.5% of Group A and 58.3% of Group B, while longitudinal pancreaticojejunostomy was done in 37.5% and 41.7%, respectively. POPF occurred in 16.7% of Group A and 25.0% of Group B, with no significant difference in severity. Other postoperative complications (vomiting, diarrhoea, wound issues, respiratory infections) were similar between groups. However, Group A had a significantly shorter hospital stay (9.33±3.75 days) than Group B (12.3±3.46 days). Conclusions: Early oral feeding after pancreaticoenteric anastomosis is safe and feasible. It shortens the hospital stay without increasing other post-operative complication.